Pulmonary exposure to cellulose nanocrystals caused deleterious effects to reproductive system in male mice - Farcas, Mariana T.; Kisin, Elena R.; Menas, Autumn L.; Gutkin, Dmitriy W.; Star, Alexander; Reiner, Richard S.; Yanamala, Naveena; Savolainen, Kai; Shvedova, Anna A. (Journal of Toxicology and Environmental Health, Part A, 2016)
Over the past several years there has been an increased number of applications of cellulosic materials in many sectors, including the food industry, cosmetics, and pharmaceuticals. However, to date, there are few studies investigating the potential adverse effects of cellulose nanocrystals (CNC). The objective of this study was to determine long-term outcomes on the male reproductive system of mice upon repeated pharyngeal aspiration exposure to CNC. To achieve this, cauda epididymal sperm samples were analyzed for sperm concentration, motility, morphological abnormalities, and DNA damage. Testicular and epididymal oxidative damage was evaluated, as well as histopathology examination of testes. In addition, changes in levels of testosterone in testes and serum and of luteinizing hormone (LH) in serum were determined. Three months after the last administration, CNC exposure significantly altered sperm concentration, motility, cell morphology, and sperm DNA integrity. These parameters correlated with elevated proinflammatory cytokines levels and myeloperoxidase (MPO) activity in testes, as well as oxidative stress in both testes and epididymis. Exposure to CNC also produced damage to testicular structure, as evidenced by presence of interstitial edema, frequent dystrophic seminiferous tubules with arrested spermatogenesis and degenerating spermatocytes, and imbalance in levels of testosterone and LH. Taken together, these results demonstrate that pulmonary exposure to CNC induces sustained adverse effects in spermatocytes/spermatozoa, suggesting male reproductive toxicity.